No Association of Latent Membrane Protein 1 (LMP1) Gene Expression of Epstein-Barr Virus and Oxidative Stress Production in Normal Nasopharyngeal Cell - Mohd Aminudin, Mustapha; Sim, Sai-Peng (Japan University of Health Sciences & Japan International Cultural Exchange Foundation, 2021)
Objective: To evaluate the effect of LMP1 gene expression on oxidative stress generation in normal nasopharyngeal cell. Material and Methods: LMP1 gene were established in pTracer and pcDNA form. The cell then transfection into normal nasopharyngeal cell line. Level of reactive oxygen species (ROS) will be assessed by measuring the fluorescence generated by the chemical 2',7'-Dichlorohydrofluorescein diacetate (DCFH-DA) for pcDNA and cell rox for pTracer. Association of LMP1 gene expression and oxidative stress level were calculate by comparing mean of pTracer and pcDNA with LMP1 gene and without LMP1 gene by use independent Sample T test. Results: There were no association between LMP1 gene expression in both pTracer LMP1 and pcDNA LMP1 compare to vector control cells in normal nasopharyngeal cell. Conclusion: Our results show that, there are no association of LMP1 gene expression and oxidative stress production in normal nasopharyngeal cell thus support that LMP1 gene.